Taxonomy, phylogeny and host plants of some Abia sawflies (Hymenoptera, Cimbicidae) - Liston, Andrew D.; Savina, Henri; Nagy, Zoltán Tamás; Sonet, Gontran; Boevé, Jean-Luc (Zootaxa, 2014)
We briefly review the taxonomy of Abia, and attempt to clarify their systematics by phylogenetic tree reconstructions inferred from three (nuclear and mitochondrial) genes of some West Palaearctic and Nearctic species. The main question which we asked is whether the distinction, made by several authors, of two genera within this group is justified. Based on the species here sampled, our results strongly support a clade recognised widely in earlier literature as Abia or Abia (Abia), but do not always support another clade, Zaraea or Abia (Zaraea), as monophyletic. In the interests of nomenclatural stability and for other practical reasons, the two nominal genera should be treated as synonyms. Host plant associations may be useful in the systematics of Abia species, but this topic requires further investigation and inclusion of more species in phylogenetic analyses.